A importância da motivação e das estratégicas de aprendizagem para o êxito escolar - Stefani, Andressa Karina (2016)
Motivation is the impulse that moves people in the search for their goals. It can be characterized as an intrinsic, when we do something for ourselves and extrinsic, when we do something for others, waiting for recognition or rewards. Because the subject is rarely addressed in the area of Education, became interested in researching into this matter and learning strategies that compose and make the students conquer academic achievement. Objectives: To assess the importance of motivation (intrinsic and extrinsic) for students of teaching and learning of secondary school and investigate the strategies that contribute to academic achievement. Method: Descriptive cross-sectional study performed at the following private school, Central de Estudos (tuition classes), which was attended by 30 students from 6th to 9th grade. For data collection, students answered, singly, Identification Form/ Questionnaire; Motivation Assessment Scale - EMA-EF and Learning Strategies - EAVAP-EF. Results: Of the 30 students who participated in the research, 40% (N=12) were female and 60% (N=18) male. The mean age among them was 12.3 ± 1.10 years. In group 1 (G1 = no difficulties), 11% (N=2) were boys and 25% (N=3) girls. In group 2 (G2 =pedagogical difficulties), 72% (N=13) were boys and 58% (N=7) girls. In group 3 (G3=disorders), 17% (N=3) were boys and 17% (N=2) girls. The results regarding the intrinsic motivation for boys indicated a significant difference (p=0.0009) between the groups, the mean being obtained higher in G1. For girls, there was no statistically significant difference between groups (p=0.1028). Regarding the extrinsic motivation for boys, there was a statistically significant difference between the groups (p=0.0228), the average obtained being lower in G3. For girls, there was no statistically significant difference between groups (p=0.5137). Regarding the learning strategies, a significant difference was found in the comparison between the groups (p=0.0024), G1 being the group that used the most strategies. In the subscale of absence of dysfunctional metacognitive strategies, a significant difference (p=0.0024) was found between the groups, with G1 appearing less or not using these strategies. As for cognitive, there was a significant difference (p=0.0066) between the groups, the mean being higher in G1. Regarding the metacognitive, there was no statistically significant difference between the groups (p=0.3408). Conclusion: Male students are more likely to attend supplementary classes than female students. Students are more motivated extrinsically. Students in the initial of secondary school (6th and 7th grades) were more motivated. Most of the students who participated in the study use learning strategies at the time of the study, with students ages 11 to 13 becoming more strategists.